Composite conchal loss from Bluetooth headset device: An interesting case report - Verma, Mukta; Mishra, Brijesh; Palmo, Dekid; Karmaker, Shilpi (Indian Journal of Case Reports, 2018)
It is a well-known fact that talking on the phone while driving increases the risk of an accident. Bluetooth headset provides simple and uncomplicated route to hands-free communication. While driving, the use of hands-free phone devices such as earpieces and Bluetooth headset is equally as dangerous as talking on a cell phone normally. Here, we are reporting a very unique case of a 25-year-old male who sustained severe ear injury (full-thickness conchal defect of the size of earpiece of Bluetooth headset device; a very unusual mechanism of injury) in a road traffic accident while wearing a Bluetooth headset device. Two-stage repair was done using a retroauricular flap for full-thickness conchal defect. The post-operative cosmetic outcome achieved by this technique was satisfactory.